Allogeneic stem cell transplantation for refractory acute myeloid leukemia: a single center analysis of long‐term outcome. (24th March 2015) - Hemmati, Philipp G.; Terwey, Theis H.; Na, Il‐Kang; Jehn, Christian F.; le Coutre, Philipp; Vuong, Lam G.; Dörken, Bernd; Arnold, Renate
Abstract: For patients with refractory acute myeloid leukemia (AML), allogeneic stem cell transplantation (alloSCT) represents the only curative approach. We here analyzed the long‐term outcome of 131 consecutive patients with active AML, which was either primary refractory or unresponsive to salvage chemotherapy, transplanted at our center between 1997 and 2013. After a median follow‐up of 48 months for the surviving patients, disease‐free survival (DFS) at 5 yr post alloSCT was 26% (94% CI: 17–35). Relapses, most of which occurred within the first 2 yr from transplant, were the predominant cause of treatment failure affecting 48% (95%CI: 40–58) of patients, whereas non‐relapse mortality was 26% (95%CI: 20–36) at 5 yr and thereafter. A marrow blast count ≥20% before alloSCT was an independent prognosticator associated with an inferior DFS (HR: 1.58, P = 0.027), whereas the development of chronic graft‐ versus ‐host disease (cGvHD) predicted an improved DFS (HR 0.21, P < 0.001) and a decreased relapse incidence (HR: 0.18, P = 0.026), respectively. These results indicate that alloSCT represents a curative treatment option in a substantial proportion of patients with refractory AML. A pretransplant blast count <20% before alloSCT and the development of cGvHD are the most important predictors of long‐term disease control.